Lightweight screed containing cork granules: mechanical and hygrothermal characterization - Moreira, A; António, J; Tadeu, A (Cement and Concrete Composites, 2014)
This paper presents the results of an experimental study on the use of expanded cork granule waste with cement-based mixtures to produce lightweight screeds as an overlay of a structural concrete slab. Lightweight screeds (LWSs) were made with Portland cement, sand, expanded cork granules (ECG) and water. These cork particles are industrial waste and are still a completely natural material even after industrial processing. The experiments were carried out on 3 cement dosages of 150 kg/m3, 250 kg/m3 and 400kg/m3, incorporating expanded cork granules as replacement of part of the sand. Three additional mixtures without cork were prepared and used as reference. They had the same cement content as the lightweight ones. Hardened density, compressive strength, thermal conductivity, water vapor permeability, adsorption isotherms and water absorption by partial immersion of the mixtures were determined. Results show that the addition of expanded cork granules affects the screeds by decreasing their density, compressive strength and thermal conductivity while increasing their water vapor permeability.
Keywords: expanded cork aggregates; hygrothermal properties; lightweight screed; mechanical properties

Thermal delay provided by floors containing layers that incorporate expanded cork granule waste - Tadeu, A; Moreira, A; António, J; Simões, N; Simões, I (Energy and Buildings, 2014)
This paper reports the computation of the thermal delay provided by concrete floors built with layers of cork and lightweight screed that incorporate expanded cork granule waste. The heat transfer by conduc- tion across these multilayer systems is simulated analytically under unsteady boundary conditions. The thermal delay is computed for multilayer concrete floors with varying numbers of layers and layer thicknesses. The mass density and thermal conductivity of the various materials were determined experi- mentally. Given its heterogeneity, the specific heat of the lightweight screed was obtained indirectly using both the experimental results and the analytical model. The results obtained show the potential of these composites in applications for increasing the thermal performance of concrete floors, in particular the thermal delay and thermal resistance. The results show that the contribution of the insulating lightweight screed material’s properties to thermal delay is more relevant in systems composed of few layers. The constructive solutions composed of a greater number of layers present higher thermal delay value.
Keywords: Analytical solutions; Building multilayer floors; Expanded cork; Frequency domain; Thermal delay; Transient heat conduction